Predictors, descriptors and components of emotional burnout in psychiatrics during the war: interrelationships, complex and mathematical models of development and prognosis - Levin, Тарас (Psychosomatic Medicine and General Practice, 2023)
The aim of the work was to identify predictors, descriptors and components of emotional burnout (EB) in psychiatrists during the war, to understand the interrelationships between them as a basis for building therapeutic approaches to the prevention and elimination of EB manifestations in this contingent. Contingent and research methods. The study sample, which was formed in compliance with the principles of biomedical ethics and based on informed consent, consisted of 120 psychiatrists who worked in the city of Kyiv in the period from February 24, 2022, during 2022. The criterion for stratification of the examined into groups was the presence and severity manifestations of professional maladjustment (PM) in psychiatrists, which reflected the level of their EB. According to the obtained results, the examinees were divided into three groups: the first group, OG1 – 30.8% (37 people) – doctors without signs of PM, and a low level of EB; the second group, OG2 – 47.5% (57 people) – persons with signs of PM, and a moderate level of EB; the third group, OG3 – 21.7% (26 people) – respondents with clinically defined and pronounced PM, and a high level of EB. Clinical-psychopathological, psychometric and psychodiagnostic research methods were used to assess the state of the parameters that make up the components of EB. Statistical analysis of the obtained results was performed using the non-parametric Mann-Whitney test (determination of differences) and the method of Spearman's rank correlations (estimation of correlations). The results. In the genesis of the development and progression of EB in psychiatrists during the war, the personal, psychopathological, psychosocial, professional and emotional-interpersonal indicators of their life activities are involved. The defining deficit of both the general level of emotional intelligence (EI) and its individual components is the basis for the formation of EB, with the progression of which the indicators of EI decrease even more, giving a start to the development of PM and starting a vicious circle of pathological interactions. The progression of EB leads to a significant imbalance in the structure of EI, namely, a significant decrease in empathy against the background of high values of the ability to recognize the emotions of other people as a professional skill, which, on the one hand, contributes to the strengthening of symptomatic in all clusters of EB, and, on the other hand, becomes a pathogenetic factor in its development and progression. PM is considered by us as a basic descriptor of EB, because it is from it that the first negative manifestations of the imbalance of the processes of performing professional duties and internal resources begin, which will ensure their optimal implementation. That is why determining the state of PM and its prognosis makes it possible to improve the quality of detection of its manifestations and to prevent the development or progression of EB in psychiatrists, as well as to prevent the development of other adverse changes from the side of psychopathological, psychosocial, etc. components of EB. Based on the possibility of identifying 4 risk groups for the development of PM, as a basic descriptor of EB, which is provided using a mathematical model of its development, 4 therapeutic strategies of diagnosis, therapy and prevention are proposed as part of the provision of specialized medical assistance to psychiatrists during the war. Conclusion. The identified regularities should be considered when developing treatment and rehabilitation measures for psychiatrists with manifestations of PM and EB.